THE EFFECT OF SOLVABILITY ON ASSET MANAGEMENT ON THE OBLIGATION OF SALATIGA CITY GOVERNMENT: (Empirical Study on Salatiga City Government for the 2021-2022 Period) - Saputri, Septia Ragil; Sari, Kamala Aprelia; Bharata, Risma Wira (JOURNAL OF HUMANITIES, SOCIAL SCIENCES AND BUSINESS, 2023)
The financial statements of local governments include assets that represent their economic wealth, which are presented in the balance sheet. However, the balance sheet of Salatiga City's local government financial statements shows an increase in inventory, long-term investments, fixed assets, and other assets. This study aims to examine the financial condition of the Salatiga City area and assess the Salatiga City Government's ability to fulfill its debts or obligations using the solvency ratio. The research method employed in this study is quantitative with a descriptive approach, involving the analysis of numerical data through calculations. The results indicate that the financial condition of the Salatiga City Regional Government demonstrates optimization in the management of current assets, as evidenced by a decrease in the solvency ratio. However, the Salatiga City Regional Government should implement strategies and improve the management of current assets and cash to enhance its ability to meet short-term and long-term financial obligations. The decline in asset value in 2021 in the Salatiga City Regional Government can be attributed to a decrease in current assets and cash.